2021
DOI: 10.2188/jea.je20210066
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Dispatches for Suicide Attempts During the COVID-19 Outbreak in Okayama, Japan: A Descriptive Epidemiological Study

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…According to a meta-analysis ( Prati and Mancini, 2021 ), the role that gender plays in depression during the COVID-19 pandemic is not universally known; its impact depends on cross-cultural differences, compared with the international prevalence of depression ( Fruehwirth et al, 2021 ; Ochnik et al, 2021 ). One local study in Japan ( Habu et al, 2021 ) reported that the number of emergency dispatches related to suicide attempts increased in 2020 compared to the previous 2 years, especially among women and those aged 25–49 years. The authors concluded that this increase may be partly explained by hardships, such as economic losses or reduced social ties, during the COVID-19 outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis ( Prati and Mancini, 2021 ), the role that gender plays in depression during the COVID-19 pandemic is not universally known; its impact depends on cross-cultural differences, compared with the international prevalence of depression ( Fruehwirth et al, 2021 ; Ochnik et al, 2021 ). One local study in Japan ( Habu et al, 2021 ) reported that the number of emergency dispatches related to suicide attempts increased in 2020 compared to the previous 2 years, especially among women and those aged 25–49 years. The authors concluded that this increase may be partly explained by hardships, such as economic losses or reduced social ties, during the COVID-19 outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies examined deaths of despair by population characteristics. Eighteen studies assessed the difference in sex and 14 in age groups for suicide death in Japan 24,47,53,55-57,88 , Australia 58,59 , US 61,89 Peru 51,52 , Korea 30 , Norway 38 , China 49 , India 48 and Italy 32 . Studies conducted in Japan and Korea showed that the suicide rate significantly increased or showed higher rates among women and younger age groups than men and older age groups.…”
Section: Resultsmentioning
confidence: 99%
“…Of 40 studies that examined suicide, four were case reports/series [41][42][43][44] , and 11 studies did not conduct any inferential analysis (testing hypotheses statistically) [30][31][32][33]37,38,[45][46][47][48] . Overall, 15 countries studied, of which seven (including case report study design) were in low-to uppermiddle-income countries 33,37,43,44,[49][50][51][52] and the remaining were in high-income countries.…”
Section: Suicide Deathsmentioning
confidence: 99%
“…There have also been reports of some suicide attempts who were positive for Covid-19 and had no previous psychiatric history [88,89]. In addition, it has been suggested that suicide attempts in population increased as related to economic losses or reduced social ties during the Covid-19 outbreak [90].…”
Section: Mental Problems Due To Chronic Stress and Social Isolationmentioning
confidence: 99%